Tính chất chịu oxi hóa nhiệt và khả năng chống cháy của vật liệu nanocompozit trên cơ sở polyme blend polyetylen ghép silicon/polyvinylclorua và nano-clay - Minh, Đào Thế; Hà, Chu Xuân; Hưng, Hoàng Tuấn; Kháng, Đỗ Quang (Vietnam Journal of Chemistry, 2014)
The aims of this work are to study the thermo-oxidative resistance property and the flame resistance ability of new nanocomposite materials based on silicone grafted polyethylene (silicone-g-PE)/polyvinylchloride (PVC) blend and nano-clay. The nanocomposites were prepared by Haake internal mixer with different silicone-g-PE/PVC and clay contents. The obtained results showed that the 80 silicone-g-PE/20 PVC/3 clay nanocomposite (%) was good resistant to 136 oC for 168 hours and the burning rate of the new nanocomposite was 9 mm/minute, about 8.2 times smaller in comparison with that of silicone-g-PE (73.8 mm/minute). Keywords: Silicone-g-PE, PVC, nano-clay, nanocomposite, thermo-oxidative resistance property, flame resistance ability.